Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Division) dalam Meningkatkan Aktivitas dan Hasil Belajar - Sayyidatul Karimah (Universitas Pekalongan, 2013)
This study aimed to: improve the activity and learning outcomes of students graders XI MA Tholabuddin Masin Warungasem on materials Trigonometry. This study is a Classroom Action Research consist of pre-cycle, cycle I and cycle II. The mean of test scores of pre-cycle 6,29. Students who get grades below 6,1 by 11 people or 45,83%. The results of this study have not been satisfaction and more than 50% of students who have not been thoroughly studied. The facts show that the students graders XI can not solve the given problem good, less willing to perform in front of the class, ask the teacher more less active, and unwilling to share their ideas. Therefore, to improve the activity and learning outcomes need to be applied model of cooperative learning type STAD. The results at cycle I show that mean the interaction of students 68,35% which the interaction of students with the teacher 65,42% and interactions between each students 71,28%. The mean of test quiz is 6,83. There are 3 groups as Good team, and 3 groups as Great Team. The mean of the test evaluation 6,94 with 70,83% completeness. The results of the reflection on cycle I still need the cycle process to show that the activity and learning outcomes improve as expected. The results at cicle II show that mean the interaction of students is 80,03% has achieved successfully which the interaction of students with teacher 78,96% and the interaction between students 81,10%. The mean of test quiz 8,04 with 3 groups as Good Team, and 3 groups as Great Team. The mean of test evaluation 7,95 with 87,5% completeness. The results of the reflection on cycle II show that the activity and learning outcomes of students with models of type STAD improves as expected. The results of calculation the response to the questionnaire that 89,59% of students satisfied with the cooperation in cooperative learning type STAD, 70,84% students brave to ask and respond the opinion, 83,34% students happy with the group award. Students clear with the material that has been delivered as much as 70,83%. Studentss are more motivated to learn as much as 87,5%. Students are satisfied with the quiz as much as 77,47%. Students are pleased with the presentations in class as much as 58,34%, and students are more appreciative of other student's opinions as much as 62,5%. It can be concluded that the learning of mathematics by using cooperative learning type STAD, activities and student learning outcomes can be improved or higher.